2010
DOI: 10.1177/0886260510372943
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Sexual Abuse Associated With Dating Partner Violence and Suicidal Ideation in a Representative Household Sample in Hong Kong

Abstract: This study investigated the prevalence and impact of childhood sexual abuse (CSA) on future intimate partner violence (IPV) in dating relationship in Hong Kong, China. A total of 1,154 Chinese adult respondents engaged in dating relationships were interviewed face-to-face about their CSA histories, childhood witnessing of parental violence, adult sexual victimization (ASV) by others and IPV victimization with their current dating partner. Self-reports also measured levels of suicidal ideation, self-esteem, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…Yet, some factors of this inclusive model still await further investigation before it can be fully applied. It is to be noted that these models were mainly derived from studies involving female participants due in large part to the absence of sufficient empirical data available for adolescent boys.Consistent with these theoretical models, previous research on adult samples has clearly established the association between CSA and risk of revictimization in adulthood (Afifi et al, 2009;Chan, Yan, Brownridge, Tiwari, & Fong, 2011;Coid et al, 2001; Daigneault, Hébert, & McDuff, 2009;DiLillo, Giuffre, Tremblay, & Peterson, 2001;Messman-Moore & Long, 2000;Ports, Ford, & Merrick, 2016) and, more specifically, with intimate partner violence (for a review see Capaldi, Knoble, Shortt, & Kim, 2012). However, just as with the theories, the majority of these studies have focused primarily on samples of female participants.…”
mentioning
confidence: 85%
“…Yet, some factors of this inclusive model still await further investigation before it can be fully applied. It is to be noted that these models were mainly derived from studies involving female participants due in large part to the absence of sufficient empirical data available for adolescent boys.Consistent with these theoretical models, previous research on adult samples has clearly established the association between CSA and risk of revictimization in adulthood (Afifi et al, 2009;Chan, Yan, Brownridge, Tiwari, & Fong, 2011;Coid et al, 2001; Daigneault, Hébert, & McDuff, 2009;DiLillo, Giuffre, Tremblay, & Peterson, 2001;Messman-Moore & Long, 2000;Ports, Ford, & Merrick, 2016) and, more specifically, with intimate partner violence (for a review see Capaldi, Knoble, Shortt, & Kim, 2012). However, just as with the theories, the majority of these studies have focused primarily on samples of female participants.…”
mentioning
confidence: 85%
“…Child sexual abuse (CSA) is a significant public health problem with negative consequences for child victims around the world. Previous research in China and other cultures has shown that the consequences of CSA include a wide range of mental, physical and social problems, such as depression, anxiety, behavioral problems, drug abuse, sexually transmitted diseases, and interpersonal relationships (Chen, Dunne, & Han, 2006;Homma, Wang, Saewyc, & Kishor, 2012;Hornor, 2010;Ko Ling, Yan, Brownridge, Tiwari, & Fong, 2011;Lin, Li, Fan, & Fang, 2011;Maniglio, 2009;Sun, Dong, Yi, & Sun, 2006;Tsutsumi, Izutsu, & Matsumoto, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Perinatal substance use and childhood maltreatment experiences. With respect to hyperkatifeia as a potential moderator of the relationships between perinatal substance use and childhood maltreatment experiences, a total of 18 articles, including 6 with perinatal participants, 67,[69][70][71][72]76 6 including adolescents, 6,[78][79][80][81]83 and 6 studies including females of reproductive age (not in perinatal or adolescent categories) 8,59-63 supported this relationship. Findings in people exposed to early adverse experiences included earlier initiation of substance use (⩽14yo), "use to cope" in adolescents, increased rates of depression and suicidal ideation, 8 higher rates of early sex or pregnancy, 67 depressive symptoms partially the moderating dose-response relationship between adverse early experiences and perinatal substance use in a longitudinal cohort, 69 the role of PTSD symptoms in the cycle of substance cravings, use, and withdrawal during pregnancy in 2 studies using ecological momentary assessment, 70,76 interaction of interpersonal sensitivity and maternal stress with perinatal cocaine use, 71 and associations of maternal early adversity, perinatal substance use, and depression with offspring internalizing and externalizing symptoms.…”
Section: Hyperkatifeia As a Potential Moderatormentioning
confidence: 99%
“…6,8,9,33, With respect to the 15 articles addressing the perinatal period, [65][66][67][68][69][70][71][72][73][74][75][76][77]94 11 articles supported associations between maternal childhood maltreatment experiences and higher risk for perinatal substance use or cravings for substances. [65][66][67][68][69][70][71][72][73][74][75] Of the 17 studies focused on adolescents, 6,9,65,67,72,[78][79][80][81][82][83][84][85][86][87]94,95 13 supported a relationship between childhood maltreatment experiences and increased risk for substance use in adolescence and transitional age youth. 6,9,…”
Section: Perinatal Substance Use and Childhood Maltreatment Experiencesmentioning
confidence: 99%
See 1 more Smart Citation